Mapping, Fieldwork, and the Moravian Archives - Sciuchetti, Mark J. (Journal of Moravian history, 2022)
Moravian maps are important representations of the way eighteenth-century Moravians navigated, lived, and how they understood space and place. To explore these connections, the author discusses the benefits and limitations of examining and georectifying historical maps by cartographers such as Andreas Hoeger, Philipp Christian Gottlieb Reuter, and Georg Wenzeslaus Golkowsky.